STATE OF Т-CELLULAR IMMUNITY AT WOMEN IN A PERIMENOPAUSAL PERIOD - Sherbina, I.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The state of cellular immunity at women in a perimenopausal period with the pathological displays of perimenopausal syndrome and physiological its flow is studied.Finding is specified on oppression of immune answer at a perimenopausal syndrome. The change of immunological index correlates with the degree of clinical displays of perimenopausal syndrome.